RSA & EXTENDED EUCLIDEAN ALGORITHM WITH EXAMPLES OF EXPONENTIAL RSA CIPHERS, RSA EXAMPLE SOLUTION WITH EXTENDED EUCLIDEAN ALGORITHM - Diko, Ergin; Ibraimi, Mushab (International Scientific Journal Vision, 2023)
In inter-system connections or between any two points in communication, it is necessary to make sure that the data goes securely. This is achieved by encrypting the sent data. As the disciplines of cryptography and network security matured, more practical applications were developed that were not readily available to ensure network security. Today, encryption has become a necessity in the digital environment. In this study, basic cryptography terms are mentioned. The RSA algorithm (Rivest-Shamir-Adleman) is the basis of a cryptographic system, a suite of cryptographic algorithms used for private security services or purposes, and this allows public key encryption, widely used to secure particularly sensitive data sent over an insecure network such as the internet. Commonly used methods were examined and RSA encryption method was chosen in accordance with the purpose of the study. RSA, a public key encryption technique, is built on the difficulty of generating and processing very large integers. In this study, operations with large numbers that take a long time are completed in a short time using various methods. It has been reflected in the study by creating a more secure structure by using large prime numbers for the key generation process.